Cancer Associated Fibroblasts Promote Renal Cancer Progression Through a TDO/Kyn/AhR Dependent Signaling Pathway - Chen, Li-bo; Zhu, Shun-ping; Liu, Tian-pei; Zhao, Heng; Chen, Ping-feng; Duan, You-jun; Hu, Rong (Frontiers in Oncology, 2021)
Cancer associated fibroblasts (CAFs) play crucial roles in cancer development, however, the specific mechanisms of CAFs associated renal cancer progression remain poorly understood. Our study observed enriched CAFs in high degree malignant tumor tissues from renal cancer patients. These CAFs isolated from tumor tissues are prone to facilitate drugs resistance and promote tumor progression in vitro and in vivo. Mechanistically, CAFs up-regulated tryptophan 2, 3-dioxygenase (TDO) expression, resulting in enhanced secretion of kynurenine (Kyn). Kyn produced from CAFs could up-regulated the expression of aromatic hydrocarbon receptor (AhR), eventually resulting in the AKT and STAT3 signaling pathways activation. Inhibition of AKT signal prevented cancer cells proliferation, while inhibition of the STAT3 signal reverted drugs resistance and cancer migration induced by kynurenine. Application of AhR inhibitor DMF could efficiently suppress distant metastasis of renal cancer cells, and improve anticancer effects of sorafenib (Sor)/sunitinib (Sun), which described a promising therapeutic strategy for clinical renal cancer.